Elucidation of Antimicrobials and Biofilm Inhibitors Derived from a Polyacetylene Core - Tyler L. Skeen; Rebekah L. Gresham; Katherine A. Agamaite; Olivia M. Molz; Isabelle F. Westlake; Sage M. Kregenow; Al K. Romero; Brian M. Flood; Lauren E. Mazur; Robert J. Hinkle; Douglas D. Young (Molecules)
The development of new antibiotics with unique mechanisms of action is paramount to combating the growing threat of antibiotic resistance. Recently, based on inspiration from natural products, an asymmetrical polyacetylene core structure was examined for its bioactivity and found to have differential specificity for different bacterial species based on the substituents around the conjugated alkyne. This research further probes the structural requirements for bioactivity through a systematic synthesis and investigation of new compounds with variable carbon chain length, alkynyl subunits, and alcohol substitution. Furthermore, the research examines the activity of the new compounds towards the inhibition of biofilm formation. Overall, several key new polyyne compounds have been identified in both decreasing bacterial viability and in disrupting pre-formed biofilms. These properties are key in the fight against bacterial infections and will be helpful in the further development of new antibiotic agents.